Doxycycline Sclerotherapy of a Cervical Cystic Hygroma: A Caribbean Institution Experience - Figaro, Nicholas; Rampersad, Robbie; Juman, Solaiman (Case Reports in Otolaryngology, 2020)
Cervical cystic lymphangiomas are rare benign tumors that pose a formidable challenge to surgeons confronted with managing this uncommon entity. Due to the intimacy with which these cystic lesions blend with critical cervical structures, a considerable number of patients who undergo surgical management are often plagued with recurrence and morbidity. As a result, doxycycline sclerotherapy has become an attractive, safe, and effective alternative as a primary treatment modality in a select group of pediatric patients. This case report presents an 18-month-old patient with a large cervical cystic hygroma that was effectively treated with exclusive doxycycline sclerotherapy.